Beyond the Genome: Genetically Modified Crops in Africa and the Implications for Genome Editing. Issue 1 (5th January 2023) - Rock, Joeva Sean; Schnurr, Matthew A.; Kingiri, Ann; Glover, Dominic; Stone, Glenn Davis; Ely, Adrian; Fischer, Klara
ABSTRACT: Genome editing — a plant‐breeding technology that facilitates the manipulation of genetic traits within living organisms — has captured the imagination of scholars and professionals working on agricultural development in Africa. Echoing the arrival of genetically modified (GM) crops decades ago, genome editing is being heralded as a technology with the potential to revolutionize breeding based on enhanced precision, reduced cost and increased speed. This article makes two interventions. First, it identifies the discursive continuity linking genome editing and the earlier technology of genetic modification. Second, it offers a suite of recommendations regarding how lessons learned from GM crops might be integrated into future breeding programmes focused on genome editing. Ultimately, the authors argue that donors, policy makers and scientists should move beyond the genome towards systems‐level thinking by prioritizing the co‐development of technologies with farmers; using plant material that is unencumbered by intellectual property restrictions and therefore accessible to resource‐poor farmers; and acknowledging that seeds are components of complex and dynamic agroecological production systems. If these lessons are not heeded, genome‐editing projects are in danger of repeating mistakes of the past.